Efficacy and Accuracy of Novel Automated Mitral Valve Quantification: Three‐Dimensional Transesophageal Echocardiographic Study. Issue 5 (13th December 2015) - Kagiyama, Nobuyuki; Toki, Misako; Hara, Masahiko; Fukuda, Shuichiro; Aritaka, Shingo; Miki, Tomonori; Ohara, Minako; Hayashida, Akihiro; Hirohata, Atsushi; Yamamoto, Keizo; Yoshida, Kiyoshi
Abstract : Background: Previous studies indicated that the three‐dimensional features of the mitral valve (MV) have a significant impact on MV disease. However, quantification of MV with manual tracing software was too time‐consuming for routine clinical practice. This study was performed to investigate the efficacy and accuracy of MV quantification with a novel highly automated commercially available software package developed for this purpose. Methods: Using the manual tracing and automated package, two expert sonographers and one cardiologist individually analyzed three‐dimensional datasets acquired with transesophageal echocardiography from 74 patients (15 with functional mitral regurgitation, 32 with MV prolapse, and 27 normal subjects) retrospectively. Time for analysis and inter‐observer agreement were compared between the two methods, and agreement of measurements was analyzed using Cronbach's α. Results: Time for analysis using the automated package was significantly shorter than manual tracing (whole cohort, 260 ± 65 vs. 381 ± 68 seconds, P < 0.001; functional mitral regurgitation, 234 ± 42 vs. 378 ± 64 seconds, P < 0.001; MV prolapse, 293 ± 69 vs. 407 ± 67 seconds, P < 0.001; normal controls, 235 ± 52 vs. 351 ± 60 seconds, P < 0.001). There was good agreement among all three observers using both methods, and measurements with the automated package agreed well with the manual tracing values. Conclusions: The novel automated software package reduced time for quantification of MV with similar accuracy compared to the manual method. Automated quantification is useful and may be a key to widespread adoption of three‐dimensional quantification in clinical practice.